Organizational Change Management in Egypt; Contractors’ Perspective - Ayoub, Karim (AUC Knowledge Fountain, 2025)
Organizational change management in the construction industry is a vital process for companies to consider in their operations. Successful implementation of the process allows the companies to go a step further in the market due to their competitiveness derived from better performance and efficiency. However, applying change to the organization and introducing new structure is a challenge for any company seeking better performance, but worth it if it is implemented properly. In general, this research sheds light on the organizational change management implementation in construction contractors in Egypt. Where, this study aims to demonstrate the organizational change management initiatives and change practices carried out by contractors on their organization. In addition, the barriers hindering the changes, benefits from applying changes, the Egyptian’s culture aspect through changes were gathered and analyzed. Finally, recommendations for a successful framework was developed based on the research outcomes, which was then validated by experts. Nine interviews were conducted to gather insights on the research objectives then based on these interviews a questionnaire was prepared and distributed to 24 participants to substantiate the input gathered from the interview, with a total of 33 participants. The results acknowledge that the organizational change management practices are taking place and being implemented by the contractors in Egypt although there are significant barriers and cultural aspect impacting the changes. Major barriers are classified into three elements; resistance to accept the change, lack of awareness of the change management concept and resource allocation consequences during change implementation. Additionally, the Egyptian’s culture dominant impact is classified into three elements fear of change and uncertainty, complacent behavior without the interest of change, and mistrust. Accordingly, several recommendations for a successful framework were portrayed tackling the barriers and Egyptian’s culture impact to achieve an effective change process. Finally, the framework was validated by conducting interviews with experts to ensure the practicality and effectiveness of adopting these recommendations to overcome the barriers during changes.